從多元文化教育的觀點，看電影「馬伊娜」（Maïna）的原住民文化觀與教育應用 - 阿將伊崮喜瀾; Iku, S., Aciang (2017)
碩士 國立政治大學 傳播學院碩士在職專班 102941018 「馬伊娜」是一部典型原住民傳統生態知識（TEK）題材的獲獎電影，片中的夢占、巫師、藥物、泛靈（動植物）、規範和紋面紋身等，皆為原住民文化的共通語言，也成為本研究探討的素材，本研究擬以這部電影的原住民文化符號，探討如何透過電影或視覺媒體，傳遞多元文化教育並轉換為原住民多元文化教育的建構、設計與過程。 本研究採用文獻資料整理、符號分析和深度訪談之多元質性分析架構，首先，研究者從執導之原住民傳統知識內容的廣電節目影像資料的台灣原住民文化符號及文字調查資料作整理，其次，根據立意抽樣，分別從行政、文化、影像和教育等四個領域，深度訪談24名原住民和4名漢人，訪問他們對於馬伊娜電影與台灣原住民文化符號異同的看法，及其對原住民多元化教育的影響，並從符號關係的探討開始，持續作第二符號的心理學分析，亦即從文化敏感度、文化心理學、跨文化心理、佛氏的凝縮和轉移之雙工匠和榮格的無意識理論的角度，分別解釋當前的原住民文化現象和意識形態的結構。 結果發現台灣原住民之夢占文化為具有文化異同、層次、相對、環境影響和判定之異同；藥物文化亦具有文化異同、隱喻和轉喻、多樣性、多用途、多附加價值、專屬使用對象、不同層次療效和師承自動物等八種特色。同時，本文亦將馬伊娜電影的伊努族和因紐特族和國內各原住民族之夢占、巫覡、規範、宇宙觀和紋面紋身作比較。最後，並闡述文化起源、過程和結構的「出神入化」意涵，並對當前原住民多元文化教育的內涵和課綱作實質的建議。 “Maïna”is a award-winning film with typical Indigenous people’s traditional ecological knowledges（TEK）symbols consist of dreams, shamans, medicinal materials, code of ethics, and tattoo, these are the same culture languages for all Indigenous people. This study aims is to explore cultural symbles in Maïna’s film, and transfer the elements of multicultural education through film or visual media then transform it into the construction, design and process of Tai- wan Indigenous people’s multicultural education. In this study, the researcher use Multivariate Analysis of literature review, Symbol A- nalysis and In-depth interviews. Firstly, there’re 15 TV films produced and directed by re- searcher in term of with the theme of TK, plus the text content of 13 television films as survey data, secondly, according to the principle of Proposive Sampling, the researcher choose 24 In- digenous people and 4 non Indigenous people of senior interviewees from positions of 4 fields of administrative, cultural, image and education, to join the interview, Thirdly, through the semiotics analysis, the researcher discussed cultural symbols of the commonality between Maïna and Taiwan Indigenous people, as well as the mutilple cultural education. The process begins at the exploration of semiotics relationships, continue to explore the second symbolic psychoanalysis, from Cultural Sensitivity, Cultural Psychology, Cross Cultural Psychology, and proposed the two craftmen of Condensation and Displacement in Freud and Jung's Un- conscious theory to explain current cultural phenomenon, and the Indigenous people’s ide- ology. The results show the commonalities of dream interpretation existed with diversity, level, relative,environmental and judgment. Medicine material culture also has eight characteristics of commonality, metaphor and metonymy, diversity, multipurpose, multi-value, exclusive object used, effiency of level and learning from animals. It also compares commonalies of dream, shamans, cosmology and tattoo between Innu, Inuit and Taiwan Indigenous people. Finally, the researcher induce the origin, process and structure of Indigenous people’s cultural to a“from myth to culture”meaning and make substantive suggestions on the lessons of multicultural education. 第一章 緒論 1 第一節 研究緣起 1 第二節 為何研究電影「馬伊娜」 10 第三節 研究動機和目的 14 第二章 文獻探討 15 第一節 多元文化教育的理論基礎：批判種族理論 15 第二節 多元文化教育的意涵和內容表現 19 第三節 原住民電影的概念與發展 22 第四節 原住民題材電影與閱聽人學習的關係 28 第五節 符號學的建構與象徵 32 第六節 原住民文化媒材與多元文化教育 43 第七節 研究問題 48 第三章 研究方法 49 第一節 質性研究架構與研究流程 49 第二節 多元方法的設計與執行 51 第三節 研究資料整理與分析 71 第四章 研究資料分析（一）：「馬伊娜」電影的分析 73 第一節 「馬伊娜」電影及其重要的文化符號與象徵 73 第二節 「馬伊娜」電影和台灣原住民文化符號的比較 85 第三節 原住民文化重要符號的意涵和保存 94 第五章 研究資料分析（二）：原住民多元文化教育分析 120 第一節 從原住民各教育概況，對傳統知識課程需求與看法 120 第二節 對原住民多元文化教育的反思 126 第三節 原住民多元文化教育的文化符號不足 134 第四節 推展原住民多元文化教育之重要文化符號和資料庫 145 第六章 研究結論與建議 152 第一節 主要研究發現與意義 152 第二節 本研究之重要貢獻 170 第三節 台灣原住民族的多元文化教育的主要問題 189 第四節 研究限制與建議 197 中文文獻 209 英文文獻 217 附錄 227 1. 影像資料整理 227 2. 文字資料整理 239